FANDOM


Let \(U(x)\) be Bird's U function.

Rule 1: \(\{a\} = \{a, 1\} = U(a)\)

Rule 2: \(\{a, b\} = \{U(a), \{a, b - 1\}\}\)

Rule 3: \(\{a, b, 1\} = \{a, b\}\)

Rule 4: \(\{a, b, c\} = \{U(a), \{a, b - 1, c\}, U(c)\}\)

Growth rate is \(f_{\vartheta(\varepsilon_{\Omega_\omega + 1})}(n)\)

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.